The Effect of Profitability, Company Value, and Leverage on Company Size : (Case Study of a Retail Company Listed on The Indonesia Stock Exchange for The Period 2018–2022) - Musaharah, Arnina Apriliani Nur; Nurhasanah, Siti; Puri, Pustika Ayuning (Westscience Press, 2024)
This study aims to determine the relationship between profitability, company value and company size leverage in the Indonesian retail industry. Financial data of retail companies listed on the Indonesia Stock Exchange were analyzed using SPSS using quantitative methods and population sampling techniques. Data was analyzed using SPSS. The results of the analysis show that there is a significant relationship between these variables and the size of the company. From the regression results, it can be seen that the constant value is 6.490, while the regression coefficients of profitability (X1), company value (X2) and leverage (X3) are 0.103, -0.001 and -0.008, respectively. This shows that changes in profitability, company value, and leverage affect the size of the company. However, only profitability has a significant positive influence on the size of the company, while the value of the company and leverage have an insignificant negative influence on the size of the company. Testing using the t-test shows that the three independent variables are linearly related to the size of the company. These findings highlight the importance of effectively managing these factors in the context of a dynamic global economy, which can affect the growth and development of retail businesses. This research contributes to the strategic management literature by providing a better understanding of the factors that influence the size of companies in the retail industry. The practical implications of these findings could help managers and stakeholders make more informed decisions when managing their companies and plan more effective strategies for long-term growth.